Epidemiological Features of Kawasaki Disease in Taiwan, 1976-2007: Results of Five Nationwide Questionnaire Hospital Surveys - Hung-Chi Lue; Lei-Ru Chen; Ming-Tai Lin; Luan-Yin Chang; Jou-Kou Wang; Chin-Yun Lee; Mei-Hwan Wu (Elsevier, 2014)
Kawasaki disease (KD) affects mainly children younger than 5 years of age, leading to coronary artery lesions, and even to life-threatening myocardial infarction. In Taiwan, KD was encountered for the first time in 1976; then, it continued to occur in increasing numbers. Methods: For the survey of epidemiological features of KD in Taiwan, we conducted five nationwide questionnaire hospital surveys in 1987, 1992, 1994, 2001, and 2008, respectively. In each survey, a special questionnaire form, together with a request letter and diagnostic guidelines for KD, was sent to the chairman of the Department of Pediatrics of all hospitals with 100 or more beds in Taiwan. Results: KD patients increased to a total of 14,399 patients by 2007, with the highest number of 1018 in 2001, and the highest incidence of 66.24 per 100,000 children < 5 years of age in 2006. Of the 14,399 patients, the male-to-female ratio ranged from 1.5 to 1.7. Of these patients, 57.6-65.2% were < 2 years of age, 23.3-26.6% were 2-4 years of age, and 11.4-15.8% were ≥ 5 years of age. Coronary artery lesions were noted in 20.2-31.5% of patients. Fourteen cases expired, documenting that the fatality rate decreased from 0.4% to 0.03% during the 31 years from 1976 to 2007. Conclusion: In Taiwan, KD was encountered for the first time in 1976, and it continued to occur, reaching the highest annual incidence of 66.24 per 100,000 children < 5 years of age in 2006. In Taiwan, the first emergence of KD came in 1976; the annual increment of the incidence rate was lower (2.41 in Taiwan vs. 4.17 Japan), and no significant KD outbreak was observed in Taiwan.